A comprehensive evaluation framework for deep model robustness. (May 2023) - Guo, Jun; Bao, Wei; Wang, Jiakai; Ma, Yuqing; Gao, Xinghai; Xiao, Gang; Liu, Aishan; Dong, Jian; Liu, Xianglong; Wu, Wenjun
Highlights: Establish a comprehensive framework for model robustness, containing 23 different metrics. Provide an open-sourced platform to support easy-to-use robustness evaluation and continuous integration. Conduct large-scale experiments and provide preliminary suggestions to the evaluation of model robustness. Abstract: Deep neural networks (DNNs) have achieved remarkable performance across a wide range of applications, while they are vulnerable to adversarial examples, which motivates the evaluation and benchmark of model robustness. However, current evaluations usually use simple metrics to study the performance of defenses, which are far from understanding the limitation and weaknesses of these defense methods. Thus, most proposed defenses are quickly shown to be attacked successfully, which results in the "arm race" phenomenon between attack and defense. To mitigate this problem, we establish a model robustness evaluation framework containing 23 comprehensive and rigorous metrics, which consider two key perspectives of adversarial learning (i.e., data and model). Through neuron coverage and data imperceptibility, we use data-oriented metrics to measure the integrity of test examples; by delving into model structure and behavior, we exploit model-oriented metrics to further evaluate robustness in the adversarial setting. To fully demonstrate the effectiveness of our framework, we conduct large-scale experiments on multiple datasets including CIFAR-10, SVHN, and ImageNet using different models and defenses with our open-source platform. Overall, our paper provides a comprehensive evaluation framework, where researchers could conduct comprehensive and fast evaluations using the open-source toolkit, and the analytical results could inspire deeper understanding and further improvement to the model robustness.